2003
DOI: 10.3171/foc.2003.14.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of advanced squamous cell carcinomas of the head and neck: internal carotid artery sacrifice and extracranial–intracranial revascularization

Abstract: Object Squamous cell carcinoma (SCC) of the head and neck may involve the carotid artery (CA) in the neck or skull base. Whether tumor resection should be associated with sacrifice of the CA is debatable. Methods Records obtained in five consecutive patients (three men, and two women; mean age 58 years, range 47–69 years) treated for recurrent or progressive SCC involving the internal carotid artery (ICA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 49 publications
(63 reference statements)
1
19
0
1
Order By: Relevance
“…However, only 5 of these 9 patients were analyzed for survival outcomes; the other 4 were described as a part of a technical report. 9,11,39 The MRI studies showed that the infratemporal ICA was involved by tumor in 9 patients, the petrous ICA in 3 patients, and the cavernous ICA in 6 patients. All patients underwent preoperative angiography, but their cerebrovascular reserve was not evaluated because vascular reconstruction was planned in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…However, only 5 of these 9 patients were analyzed for survival outcomes; the other 4 were described as a part of a technical report. 9,11,39 The MRI studies showed that the infratemporal ICA was involved by tumor in 9 patients, the petrous ICA in 3 patients, and the cavernous ICA in 6 patients. All patients underwent preoperative angiography, but their cerebrovascular reserve was not evaluated because vascular reconstruction was planned in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with an artery severely affected by atherosclerosis or after carotid artery resection due to tumor invasion, vessel transplantation is the surgical mainstay of therapy (1)(2)(3)(4)(5)(6)(7). The preferred bypass substitute is the patient's own vessels.…”
mentioning
confidence: 99%
“…Fifteen articles were added to the study from searching the references of papers encountered through the literature search. After the second group reviewed the remaining 78 articles, 27 were selected that had sufficient data about extracranial‐intracranial bypass for tumors that could be analyzed in the final review (Table ) …”
Section: Resultsmentioning
confidence: 99%